A study of defects reduction in injection process of production line - Karen, Yap Chia Ern (2013)
This study was conducted to analyze various factors of defects in injection moulding process of the production line of manufacturing organization. Based on some reading material such as, journal, book and some study states that some factors such as machine, man, mould, method, technology and material caused defects in injection moulding process. The objective of this study is to determine the factors that caused defect in injection moulidng process in production line. Interview secession will be conducting with production line and several departments manager to have some discussion and observation about the study. In the nut shell, I wish that this study will be one of the references to be use in future and may be can have some improvement for this study.